EU Non-Financial Reporting Research - Albertina Monteiro; Catarina Cepêda; Amélia Silva (International Journal of Financial, Accounting, and Management, 2022)
Purpose: This paper presents a longitudinal evaluation of the research about Directive 2014/95/EU regarding Non-Financial Reporting (NFR), identifying the t theoretical approaches, methodological adopteds, and research topics. Research methodology: Data was collected from the Web of Science (WoS) database, between 2016 and 2021. The search criteria resulted in a total of 59 valid articles, after which we performed a quantitative bibliometric analysis using VOSviewer software. Results: Publications on this Directive 2014/95/EU has increased from 2015 to 2021. Findings show that most articles resorted to quantitative and qualitative methodologies, emphasizing content analysis, combined with other research methods. The frameworks based on stakeholders and institutional theories are very popular in the field. Research is focused on (1) Directive 2014/95/EU regulation, implementation, compliance, and investigation, (2) determinants and impacts of NFR, (3) NFR level/evolution and (4) reasons and skills for NFR. Papers published on EU non-financial information are very heterogeneous and lack consensus as to its impact on NFR. Limitations: This study only included the WoS database as a source of data collection, and it would be valuable in future studies to add other quality databases. Contribution: This research contributes to illuminating institutional pressures implication for NFR development. Therefore, this analysis is essential for institutions operating in accounting information standardization, as well as for information preparers given the necessity to acquire skills to ensure this new challenge related to the reporting of corporate social responsibility.